SARS-CoV-2 infection in children with rheumatic disease: Experience of a tertiary referral center - Betül Sözeri,; Ferhat Demir,; Sevinç Kalın,; Canan Hasbal Akkuş,; Enes Salı,; Deniz Çakır, (Archives of Rheumatology, 2021)
Objectives: In this study, we present our clinical severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) experience in patients with childhood rheumatic disease during novel coronavirus-2019 (COVID-19) pandemic. Patients and methods: A total of 87 patients (50 males, 37 females; median age: 12 years; range, 6.6 to 16 years) suspected of having COVID-19 at our pediatric rheumatology clinic between March 11th and October 15th 2020 were retrospectively analyzed. Demographic and clinical features, treatments, laboratory results, imaging findings, and clinical outcomes of the patients diagnosed with COVID-19 and/or multisystem inflammatory syndrome in children (MIS-C) were retrieved from the medical records. The diagnosis of SARS-CoV-2 infection was made based on the reverse transcriptase-polymerase chain reaction test. Results: The most common rheumatic diseases were juvenile idiopathic arthritis and familial Mediterranean fever (35.6% and 34.5%, respectively). Twenty-six of these patients were treated with biological disease-modifying anti-rheumatic drugs. SARS-CoV-2 infection was tested as positive in 84 (96.5%) patients. Also, 51 (58.6%) patients had an epidemiological contact to a person with COVID-19. Eighteen patients met the clinical criteria and diagnosed with MIS-C. The COVID-19 outbreak also caused exacerbation of systemic disease in 56 children due to medication cessation, postponed drug switch, or recurrent viral infection. Conclusion: Children with rheumatic disease do not appear to present a higher risk of severe COVID-19. The immunosuppressive treatments can be adjusted in case of infection; otherwise, it is not recommended to interrupt the treatments. Physicians should be cautious about the hyperinflammatory syndrome associated with COVID-19 in rheumatic children, which may be severe in this group of patients and may be confused with primary diseases.